THE PEARL OF THE CENTRAL ASIA.UZBEKISTAN-THEN AND NOW - Khamraboeva Dilnoza Lochinovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: This essay will discuss about one of the most historical places in the Central Asia which is called Uzbekistan.It will also give some useful information about the great heritage of the country and its developing way and strategy since the past.